Legal Construction of Adaptive Resilience of MSMEs in Emerging Markets: The Interaction of Financial Regulation, Organisational Governance, and Local Cultural Dynamics - Yuli Agustina; Sumiati; Siti Aisjah; Risna Wijayanti; Olena Bulhakova (PT. Islamic Research Publiser, 2026)
This study examines the legal construction of adaptive resilience among Micro, Small, and Medium Enterprises (MSMEs) in emerging markets by analysing the interaction between financial regulation, organisational governance, and local cultural dynamics. It aims to demonstrate how legal frameworks extend beyond compliance to actively shape MSMEs’ capacity to adapt, survive, and transform amid economic uncertainty, market volatility, and structural constraints. Using a socio-legal perspective, the study argues that MSME sustainability is not determined solely by economic factors, but also by how law operates within institutional practices and culturally embedded business environments. The research employs a qualitative socio-legal design that integrates normative legal analysis with empirical inquiry. Normative analysis focuses on financial and MSME regulatory frameworks, particularly their coherence, flexibility, and responsiveness. Empirical data are collected through semi-structured interviews with MSME actors, regulators, and stakeholders, supported by limited field observations. Data analysis follows an interactive model involving reduction, thematic categorisation, and interpretative synthesis, while triangulation ensures validity and analytical rigour. The findings reveal that three interconnected dimensions shape adaptive resilience. First, regulatory design—especially flexibility, proportionality, and access to financial instruments—determines the adaptive space available to MSMEs. Second, internal organisational governance, including risk management capacity and strategic leadership, influences how regulatory opportunities are translated into practical resilience strategies. Third, local cultural dynamics, such as trust-based networks, communal solidarity, and informal norms, mediate the implementation of both regulatory and governance practices. These findings confirm that resilience is not merely a market outcome, but a legally and socially embedded process. The study contributes to socio-legal scholarship by proposing an integrated framework that conceptualises adaptive resilience as a product of regulatory structures, governance mechanisms, and cultural contexts, while offering practical insights for policymakers to design more responsive legal systems that enhance MSME sustainability.